A systematic review of recent clinical practice guidelines on the diagnosis, assessment and management of hypertension. - Lubna A Al-Ansary; Andrea C Tricco; Yaser Adi; Ghada Bawazeer; Laure Perrier; Mohammed Al-Ghonaim; Nada AlYousefi; Mariam Tashkandi; Sharon E Straus (PLoS ONE)
Background Despite the availability of clinical practice guidelines (CPGs), optimal hypertension control is not achieved in many parts of the world; one of the challenges is the volume of guidelines on this topic and their variable quality. To systematically review the quality, methodology, and consistency of recommendations of recently-developed national CPGs on the diagnosis, assessment and the management of hypertension. Methodology/principal findings MEDLINE, EMBASE, guidelines' websites and Google were searched for CPGs written in English on the general management of hypertension in any clinical setting published between January 2006 and September 2011. Four raters independently appraised each CPG using the AGREE-II instrument and 2 reviewers independently extracted the data. Conflicts were resolved by discussion or the involvement of an additional reviewer. Eleven CPGs were identified. The overall quality ranged from 2.5 to 6 out of 7 on the AGREE-II tool. The highest scores were for "clarity of presentation" (44.4%-88.9%) and the lowest were for "rigour of development" (8.3%-30% for 9 CGPs). None of them clearly reported being newly developed or adapted. Only one reported having a patient representative in its development team. Systematic reviews were not consistently used and only 2 up-to-date Cochrane reviews were cited. Two CPGs graded some recommendations and related that to levels (but not quality) of evidence. The CPGs' recommendations on assessment and non-pharmacological management were fairly consistent. Guidelines varied in the selection of first-line treatment, adjustment of therapy and drug combinations. Important specific aspects of care (e.g. resistant hypertension) were ignored by 6/11 CPGs. The CPGs varied in methodological quality, suggesting that their implementation might not result in less variation of care or in better health-related outcomes. Conclusions/significance More efforts are needed to promote the realistic approach of localization or local adaptation of existing high-quality CPGs to the national context.